ANALISIS PENGARUH HARGA, KEMUDAHAN PENGGUNAAN DAN ULASAN KONSUMEN DARING TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE TOKOPEDIA DI BOGOR - Muhlis; Mujito; Novita Anggraeni; Silma Mausuli (Institut Teknologi dan Bisnis Dewantara, 2025)
This study aims to analyze the influence of price, ease of use, and online consumer reviews on purchasing decisions at the Tokopedia marketplace in Bogor. The variables studied were price, ease of use, and online consumer reviews as independent variables, while purchasing decisions were the dependent variable. A quantitative approach with a causality research strategy was used, and data was collected from 100 respondents who are Tokopedia users in Bogor using a questionnaire. The data analysis technique used was multiple linear regression analysis. The results showed that price, ease of use, and online consumer reviews each had a significant and positive effect on purchasing decisions. Furthermore, all three variables simultaneously and significantly influence purchasing decisions. The price variable was found to be the most dominant factor influencing purchasing decisions, with a regression coefficient of 0.486. The adjusted R-square value was 0.654, which indicates that 65.4% of the variation in purchasing decisions is explained by the three variables, while the remaining 34.6% is influenced by other variables not included in this study.